2011
DOI: 10.1111/j.1750-3841.2011.02088.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Xanthan and Hydroxypropyl Methylcellulose Individually Affect the Physicochemical Properties in a Model Gluten‐Free Dough?

Abstract: Two types of hydrocolloids, xanthan gum and HPMC, were individually added to a gluten-free rice cassava formulation. Based on the thermoanalytic and rheological studies on dough, as well as the bread quality studies, high methoxy HPMC at 5% addition was determined to optimally improve the bread quality when only gum addition was considered. This study indicates the potential use of high methoxy HPMC as an additive in gluten-free bread formulations prior to considering alternative proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 39 publications
12
53
0
1
Order By: Relevance
“…It is possible that the high water-binding capacity of xanthan leads to scarcity of , 3 and 4). A similar trend has been observed with low methoxy HPMC (Crockett et al 2011). The untreated PMF dough shows the lowest adhesiveness (6.3 mJ), whereas the highest value of 45.5 mJ is exhibited by the xanthan-added dough.…”
Section: Dough Characteristicssupporting
confidence: 79%
“…It is possible that the high water-binding capacity of xanthan leads to scarcity of , 3 and 4). A similar trend has been observed with low methoxy HPMC (Crockett et al 2011). The untreated PMF dough shows the lowest adhesiveness (6.3 mJ), whereas the highest value of 45.5 mJ is exhibited by the xanthan-added dough.…”
Section: Dough Characteristicssupporting
confidence: 79%
“…Furthermore, the moisture content of the breads containing HPMC gum is higher than those containing xanthan gum and that water retention capacity of the breads improve with the combined use of both gums. The findings obtained in this stage of the study are consistent with the reports of Stauffer (1990), Gallagher et al (2004) and with the findings of Rosell et al (2001), Gujral et al (2003) and Crockett et al (2011). It was further observed that combined use of hydrocolloid(s) with surfactants in dough formulation did not have a significant (P > 0.01) impact on the moisture content of breads compared to the breads made without using surfactants (Pyler 1988).…”
Section: Discussionsupporting
confidence: 82%
“…Consumers need to be educated to desire healthy home cooking or healthy promoting commercially produced foods and snacks. There are many studies reporting gluten-free breads with the addition of various hydrocolloids and leavening agents to match the characteristics of the gluten containing breads (Crockett et al, 2011;Hera et al, 2014;Sabanis et al, 2011;Schober et al, 2007). Gluten-free breads and cookies made with raw and popped amaranth flour were reported to be acceptable (Barca et al, 2010).…”
Section: Introductionmentioning
confidence: 99%